Multi-shell gold nanoparticles functionalized with methotrexate: a novel nanotherapeutic approach for improved antitumoral and antioxidant activity and enhanced biocompatibility - Denisse-Iulia Bostiog; Natalia Simionescu; Adina Coroaba; Ioana C. Marinas; Mariana C. Chifiriuc; Gratiela Gradisteanu Pircalabioru; Stelian S. Maier; Mariana Pinteala (Taylor & Francis Group, 2024)
Methotrexate (MTX) is a folic acid antagonist routinely used in cancer treatment, characterized by poor water solubility and low skin permeability. These issues could be mitigated by using drug delivery systems, such as functionalized gold nanoparticles (AuNPs), known for their versatility and unique properties. This study aimed to develop multi-shell AuNPs functionalized with MTX for the improvement of MTX antitumoral, antioxidant, and biocompatibility features. Stable phosphine-coated AuNPs were synthesized and functionalized with tailored polyethylene glycol (PEG) and short-branched polyethyleneimine (PEI) moieties, followed by MTX covalent binding. Physicochemical characterization by UV-vis and Fourier-transform infrared spectroscopy (FTIR) spectroscopy, dynamic light scattering (DLS), scanning transmission electron microscopy (STEM), and X-ray photoelectron spectroscopy (XPS) confirmed the synthesis at each step. The antioxidant activity of functionalized AuNPs was determined using DPPH radical scavenging assay, ferric ions' reducing antioxidant power (FRAP), and cupric reducing antioxidant capacity (CUPRAC) assays. Biocompatibility and cytotoxicity were assessed using MTT and LDH assays on HaCaT human keratinocytes and CAL27 squamous cell carcinoma. MTX functionalized AuNPs demonstrated enhanced antioxidant activity and a pronounced cytotoxic effect on the tumoral cells compared to their individual components, highlighting their potential for improving cancer therapy.